Teacher’s questioning skills and students’ responses in science subject based on parenting style perspectives - Nurhaty Purnama Sari; Wilda Fasim Hasibuan (University of Muhammadiyah Malang, 2019)
Parenting styles were considered as one of important factors in determining students’ performance in science, especially in elementary school. This study aimed to explain the teacher's questioning skills and student’ responses in science subject based on parenting styles in elementary schools in Batam. This descriptive qualitative research was conducted in the first semester of academic year 2017/2018 and involved four classroom teachers and 109 students. The data collection techniques used were questionnaire and observation. The findings of this study showed that the teacher questioning skills in science subject in elementary schools in Batam were good enough. Meanwhile, the highest frequent parenting style used was authoritarian (94.83%). Yet the style led the students to be less active in learning processes.